Empoderar por meio do ensino e aprendizagem da língua portuguesa no contexto de Timor-Leste - Baltazar, Alexandra Fernandes (Linguarum Arena, 2020)
In an era in which the basic rights and freedoms of human beings are the target of constant threats in the most diverse parts of the world, this paper aims to show how the teaching-learning of Portuguese as a Foreign Language (PLNM) can empower, particularly in the context of Timor-Leste. Along this path we draw a link between the teaching-learning of the Portuguese language and education as a right that gives power and enables the person to experience the benefits of other rights. This reflection stems from the work developed as a Portuguese-language trainer of teachers of the Secondary Technical-Vocacional Education in Timor-Leste between 2012 and 2014. Based on the post-method pedagogy proposal of Kumaravadivelu (2006), we sought, by creating a space in Portuguese language in one of the national newspapers of Díli, to combine the learners’ language needs with their social needs through the development of personalized activities (Tomlinson 2003) that involve learners not only cognitively but also emotionally, culturally and socially.